NOS2 expression is restricted to neurons in the healthy brain but is triggered in microglia upon inflammation. Issue 6 (25th February 2014) - Béchade, Catherine; Colasse, Sabrina; Diana, Marco A.; Rouault, Martin; Bessis, Alain
<x xml:space="preserve">Abstract</x> Nitric oxide (NO) is a diffusible second messenger with a great variety of functions in the brain. NO is produced by three isoforms of NO synthase (NOS), NOS1, NOS2, and NOS3. Although broad agreement exists regarding the expression of NOS1 and NOS3 in neurons and endothelial cells, the pattern of NOS2 expression is still controversial and remains elusive. We have now generated a novel transgenic mouse that expresses the fluorescent reporter tdTomato and the CRE recombinase under the control of the Nos2 gene regulatory regions. Such tool allows the reliable tracking of NOS2 expression in tissue and further unravels episodes of transient NOS2 expression. Using this transgenic mouse, we show that in the healthy brain, NOS2 is only transiently expressed in neurons scattered in the piriform and entorhinal cortex, the amygdaloid nuclei, the medial part of the thalamus, the hypothalamus, the dentate gyrus, and the cerebellum. NOS2 expression was rarely detected in microglia. We further show that inflammation, induced by intracerebral injection of LPS and IFNγ, triggers transient expression of NOS2 in microglia but not in neurons. This novel transgenic tool has thus allowed us to clarify the NOS2 expression pattern and its differential profile in neurons and microglia in healthy and inflammatory conditions. GLIA 2014;62:956–963